Money laundering in global trade and the role of financial technology: the structured reviews - Mohamed Yousop, Nur Liyana; Ab Razak, Nazrul Hisyam; Noordin, Bany Ariffin Amin (Asian Economic and Social Society, 2024)
Money laundering in international trade facilitates the concealment of illicit funds through the manipulation of trade invoices and the exploitation of regulatory gaps. Addressing this issue involves improving traceability through financial technology, a promising solution. However, the adoption of such technology poses inherent risks and challenges that require careful consideration. This review synthesises knowledge on trade-related money laundering and financial technology, highlighting critical areas for additional research and improvement. Employing a Preferred Reporting Item for Systematic Reviews and Meta-Analyses (PRISMA) approach, academic databases, including Scopus and Web of Science (WoS), were systematically searched to identify relevant studies and articles. Advanced search techniques using keywords such as money laundering, trade-based money laundering, and financial technology resulted in the identification of 57 articles for eligibility. After excluding 20 articles due to being out of the field, having titles not significantly related, or abstracts not aligning with the study's objective, 37 eligible articles and conference proceedings were further examined. Two main themes were developed, concluding that the convergence of money laundering through digital trade and financial technology requires collaborative efforts among regulatory bodies, financial institutions, and technology experts. Such collaboration is essential to balance innovation and security, ensuring stability and prosperity in global economies.